2012
DOI: 10.1016/j.neuroimage.2012.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Anti-correlated networks, global signal regression, and the effects of caffeine in resting-state functional MRI

Abstract: Resting-state functional connectivity magnetic resonance imaging is proving to be an essential tool for the characterization of functional networks in the brain. Two of the major networks that have been identified are the default mode network (DMN) and the task positive network (TPN). Although prior work indicates that these two networks are anti-correlated, the findings are controversial because the anti-correlations are often found only after the application of a pre-processing step, known as global signal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
145
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 55 publications
19
145
0
Order By: Relevance
“…Given the absence of activation paradigm in these studies, it is hard to compare these data with those obtained in the present experimental setting. Another recent study showed that caffeine significantly enhances the detection of the known anti-correlations between the default mode network (DMN) and the task positive network (TPN) (Wong et al, 2012). Subsequently, the WM-load related an increase in functional connectivity after caffeine intake observed here cannot be attributed to a nonspecific effect of this substance.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Given the absence of activation paradigm in these studies, it is hard to compare these data with those obtained in the present experimental setting. Another recent study showed that caffeine significantly enhances the detection of the known anti-correlations between the default mode network (DMN) and the task positive network (TPN) (Wong et al, 2012). Subsequently, the WM-load related an increase in functional connectivity after caffeine intake observed here cannot be attributed to a nonspecific effect of this substance.…”
Section: Discussionsupporting
confidence: 49%
“…Several functional magnetic resonance imaging (fMRI) studies documented the decrease of connectivity and global signal amplitude in various cortical areas at resting states (Rack-Gomer et al, 2009;Rack-Gomer and Liu, 2012;Wong et al, 2012). The rare fMRI activation studies used simple perceptual tasks (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No mean global signal regression has been performed due to an ongoing dispute related to negative correlations observed after mean global signal regression (Qing, Dong, Li, Zang, & Liu, 2015; Wong, Olafsson, Tal, & Liu, 2012; Yeh, Tseng, Lin, Tsai, & Huang, 2015). (10) Data were filtered in the range between 0.01 and 0.1 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, no accepted methods are available to include individual drug concentrations in the network analysis. Further, fMRI effects, especially in pharmacological research, are potentially the result of vasodilation, and hence to changes in neurovascular coupling instead of true neural activity [Rack‐Gomer and Liu, 2012; Wong et al, 2012]. Although SSRIs do not typically alter the hemodynamic response [Feczko et al, 2012], AChEIs could increase vessel tone by contraction of the smooth muscles of blood vessels [Rosengarten et al, 2009; Stephenson and Kolka, 1990].…”
Section: Discussionmentioning
confidence: 99%